Indigenous methodologies: characteristics, conversations and contexts - Kovach, Margaret (University of Toronto Press, 2009)
« An innovative and important contribution to Indigenous research approaches, this revised second edition provides a framework for conducting Indigenous methodologies, serving as an entry point to learn more broadly about Indigenous research" (résumé de l'éditeur). Divers chapitres s'intéressent à des dimensions relatives à la recherche partenariale, participative ou collaborative » [Résumé équipe ORPCC]
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; autochtones; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; recherche en milieux de pratique; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions